The relative importance of DNA methylation and Dnmt2-mediated epigenetic regulation on Wolbachia densities and cytoplasmic incompatibility - Daniel P. LePage; Kristin K. Jernigan; Seth R. Bordenstein (PeerJ, 2014)
Wolbachia pipientis is a worldwide bacterial parasite of arthropods that infects germline cells and manipulates host reproduction to increase the ratio of infected females, the transmitting sex of the bacteria. The most common reproductive manipulation, cytoplasmic incompatibility (CI), is expressed as embryonic death in crosses between infected males and uninfected females. Specifically, Wolbachia modify developing sperm in the testes by unknown means to cause a post-fertilization disruption of the sperm chromatin that incapacitates the first mitosis of the embryo. As these Wolbachia-induced changes are stable, reversible, and affect the host cell cycle machinery including DNA replication and chromosome segregation, we hypothesized that the host methylation pathway is targeted for modulation during cytoplasmic incompatibility because it accounts for all of these traits. Here we show that infection of the testes is associated with a 55% increase of host DNA methylation in Drosophila melanogaster, but methylation of the paternal genome does not correlate with penetrance of CI. Overexpression and knock out of the Drosophila DNA methyltransferase Dnmt2 neither induces nor increases CI. Instead, overexpression decreases Wolbachia titers in host testes by approximately 17%, leading to a similar reduction in CI levels. Finally, strength of CI induced by several different strains of Wolbachia does not correlate with levels of DNA methylation in the host testes. We conclude that DNA methylation mediated by Drosophila’s only known methyltransferase is not required for the transgenerational sperm modification that causes CI.